Perbedaan Tanda Vital Sebagai Respon Kecemasan Pada Pasien Preoperatif - Irwanto; Narmawan; Indriastuti, Diah (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2020)
Preoperative patients who will undergo the first surgery will feel anxious which results in the body'sresponse in the form of increased blood pressure, pulse and breathing. If it's excessive, the work of the heartincluding in body's oxygen requirements will increase. This study aims to determine the differences in vitalsigns as an anxiety response in preoperative patients. This study is a comparative descriptive study of 44preoperative patients. Subjects were withdrawn from the population by accidental sampling, then measuredblood pressure, pulse and breathing twice, the day before surgery, and five minutes before anesthesia.Wilcoxom test results show the value of ρ <α (ρ <0.05) which means there are differences in blood pressure(Sistol-Diastole), pulse frequency, and respiration before surgery and five minutes before anesthesia.Theconclusion that there are differences in vital signs in preoperative patients as an anxiety response to the daybefore surgery and five minutes before anesthesia.Recommendations need to increase awareness,understanding, insight related quality of nursing care in applying nursing care and education of thepsychological patient's preoperative.